Fungal Diseases of Khair (Acacia catechu Willd.) and their Prevention - Bakshi, B. K. (Indian Forester, 1957)
Diseases of khair (Acacia catechu) due to Fomes badius which causes heartrot and Ganoderma lucidum and Polyporus gilvus which cause root rot are described. Of these, F. badius causes serious loss to khair by decaying the heartwood which yields cutch and katha of commerce. Khair is subjected to various injuries through which F. badius infects the trees. Some of these could be controlled like illicit lopping of branches for fodder, seed collection, etc., damage to trees due to animals like porcupines by providing a porcupine-proof fence in the plantations. Freedom from injury to khair will greatly minimise infection due to F. badius. Sporophores of the fungus which develop readily on affected trees could be easily knocked off, collected and destroyed. This will reduce the inoculum and check spread of the disease. Khair raised as a pure crop or in admixture with shisham only is more susceptible to attack not only by F. badius but also by G. lucidum and P. gilvus which are serious pathogens on shisham. To minimise the diseases due to all the three fungi it is necessary to raise khair in plantations in mixture with many species as practised in Uttar Pradesh in the present day. A list of 17 such species indicating their liability to attack by the three pathogens is given. Some of these species are resistant while others are susceptible to attack by the three fungi in various degrees. Khair should be raised in mixtures with these on a checkerboard method keeping in view the fact that susceptible species, particularly those attacked by root parasites like G. lucidum and P. gilvus are not concentrated at one place. Working Plans should prescribe removal of all diseased trees including those below the exploitable diameter class.